Remaja Sehat melalui Edukasi Kesehatan tentang Pentingnya Buah dan Sayur - Efni, Nel; Fatmawati, Tina Yuli (Universitas Baiturrahim, 2025)
The level of vegetable and fruit consumption among Indonesian people has not yet reached the recommended figure. In fact, vegetables and fruits are important sources of vitamins, minerals, and fiber that are greatly needed by adolescents to support growth and prevent various diseases. The GERMAS program, emphasizes the importance of consuming vegetables and fruits every day. The recommendation for vegetable consumption is 3-4 servings per day, while consuming fruit is 2-3 servings per day. The purpose of this community service is to increase adolescent knowledge about the importance of consuming vegetables and fruits. This activity was carried out at SMP Pertiwi with 30 student participants. The methods used included lectures, discussions/questions and answers with leaflets and modules. The results of the activity showed an increase in student knowledge about the importance of consuming vegetables and fruits. In the pre-test, 22 people (74.4%) had insufficient knowledge. After being given education, the knowledge increased to 26 people (86.6%). Through education, adolescents are expected to understand the importance of the role of fruits and vegetables in supporting growth, preventing disease, and improving quality of life.